THE EFFECT OF STEAM ON STUDENT LEARNING ACTIVITIES IN ELEMENTARY SCHOOL - Nina Rahayu; Dara Amanahtillah; Febriyantika Wulandari; Jelita Jelita (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
The low learning activity of grade V students of MIIT Al-Mubarak Langsa related to science is due to the lack of active students in learning so that it is necessary to have an approach that can increase student learning activities STEAM. This study aims to determine the effect of STEAM on student learning activities in science learning grade V MIIT Al-Mubarak Langsa in the 2022/2023 school year. This type of research is quantitative research. All fifth grade students of MIIT Al-Mubarak Langsa totaling 34 students are the population while the sample of this study is students from two classes, namely 17 VA class students as the experimental class and 17 VB class students as the control class. Data collection techniques in this study were in the form of observation sheets, with data analysis using SPSS 24. Hypothesis testing using the Independent Sample Test t test. Based on the hypothesis testing of learning activities in experimental and control classes, the tcount> ttable is 20.873> 2.036 and a significant value of 0.00 <0.05. So it can be concluded that HO is rejected and Ha is accepted at the significance level a=0.05, which means that there is an effect of the STEAM approach on student learning activities.Keywords: Activity, Student Learning, Science, STEAM